Kajian Sosiopragmatik Iklan Dakwah tentang Riba - Fatmahwati A. Adnan (Badan Pengembangan dan Pembinaan Bahasa, 2021)
The purpose of this study is to find out the types of speech acts and the pragmatic power of the proselytism advertisement on usury. The qualitative approach is used in this study. The method used is the descriptive phenomenological method. Data regarding Islamic proselytism advertisements are collected from field studies and documentation, while pragmatic power data are obtained through interviews. The research findings reveal that the speech act used the most is the assertive speech act, namely presenting facts, information, knowledge, and Islamic law on usury by including arguments and evidence based on the Quran and Hadith. The data regarding the pragmatic power obtained from the respondents show that 46% of respondents